Temporal and spatial patterns in the recruitment of Balanus glandula and Balanus laevis (Crustaceae, Cirripedia) in Comodoro Rivadavia harbor (Chubut, Argentina) - Rico, Alicia (2001)
The presence of Balanus glandula Darwin and B. laevis Bruguière is reported for the first time in Comodoro Rivadavia harbor (Province of Chubut, Argentina). Recruitment was studied during an annual period at three levels: upper and middle intertidal, and subtidal. Recruit density was around 30 times higher in B. glandula than in B. laevis. Both species had maximum recruitment during spring, but showed clear differences in vertical zonation. B. glandula recruited exclusively in the intertidal zone, whereas B. laevis was found mainly in subtidal samples, with very low degree of overlapping. High variability in recruitment was observed at a scale of 20 m.